On the tolerance of charophytes to high-nitrate concentrations. Issue 1 (2nd January 2018) - Rodrigo, María A.; Puche, Eric; Rojo, Carmen
ABSTRACT: Currently a debate exists about whether the reduced growth of macrophytes with increased nitrogen loading in shallow ecosystems is determined by ecological or physiological factors. To discover whether nitrate in the water is detrimental per se to charophytes, we subjected Chara hispida and Chara vulgaris specimens, collected from two habitats greatly differing in nitrate concentrations (1.5 and 10 mg NO3 -N/L, annual means), to a wide nitrate range (0.5–50 mg NO3 -N/L) in two experiments (with free-floating specimens using nitrate as the sole N source, and with planted specimens, with other N sources in sediment). Charophytes grew both unplanted and planted in all treatments, and growth reductions occurred at the highest concentration in all cases. Some charophyte responses when faced with nitrate increases were different depending on (i) the species and (ii) population origin. Under the most realistic situation, the growth of both planted C. vulgaris populations was higher than that of C. hispida populations. C. vulgaris specimens from the nitrate-rich waterbody adapted best to the highest nitrate concentrations when they grew floating. Despite charophytes being vital and growing under high-nitrate concentrations in short-term laboratory experiments, such a situation in the environment may eventually not be sustainable, since ecological factors act in the field.